2015
DOI: 10.1155/2015/529059
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization ofGeobacillus stearothermophilusSR74 Recombinantα-Amylase inPichia pastoris

Abstract: Geobacillus stearothermophilus SR74 is a locally isolated thermophilic bacteria producing thermostable and thermoactive α-amylase. Increased production and commercialization of thermostable α-amylase strongly warrant the need of a suitable expression system. In this study, the gene encoding the thermostable α-amylase in G. stearothermophilus SR74 was amplified, sequenced, and subcloned into P. pastoris GS115 strain under the control of a methanol inducible promoter, alcohol oxidase (AOX). Methanol induced reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Two criteria were emphasized when choosing the target proteins: thermostability and significant primary sequence heterogeneity between isoenzymes. As shown in Table 1 , the α-amylases from B. licheniformis (AmyL), B. subtilis (AmyE) and G. stearothermophilus (AmyS) selected for this study are reported to have temperature optima at 90 °C, 50 °C and 65 °C, respectively [ 77 79 ], while apr -encoded subtilisin from B. licheniformis has a temperature optimum at 50 °C, and the aprE -encoded protease from B. subtilis 168 has a homolog from B. subtilis A26 (91.34% identity) whose optimum temperature is at 60 °C [ 80 , 81 ]. Even though the α-amylases chosen for this study were derived from closely related organisms, their amino acid sequences differ substantially from the B. methanolicus -derived Amy, with sequence similarities of 22.47%, 27.62% and 24.86% for AmyS, AmyE and AmyL, respectively, ensuring that different signal peptides and also different model proteins were tested in B. methanolicus .…”
Section: Resultsmentioning
confidence: 99%
“…Two criteria were emphasized when choosing the target proteins: thermostability and significant primary sequence heterogeneity between isoenzymes. As shown in Table 1 , the α-amylases from B. licheniformis (AmyL), B. subtilis (AmyE) and G. stearothermophilus (AmyS) selected for this study are reported to have temperature optima at 90 °C, 50 °C and 65 °C, respectively [ 77 79 ], while apr -encoded subtilisin from B. licheniformis has a temperature optimum at 50 °C, and the aprE -encoded protease from B. subtilis 168 has a homolog from B. subtilis A26 (91.34% identity) whose optimum temperature is at 60 °C [ 80 , 81 ]. Even though the α-amylases chosen for this study were derived from closely related organisms, their amino acid sequences differ substantially from the B. methanolicus -derived Amy, with sequence similarities of 22.47%, 27.62% and 24.86% for AmyS, AmyE and AmyL, respectively, ensuring that different signal peptides and also different model proteins were tested in B. methanolicus .…”
Section: Resultsmentioning
confidence: 99%
“…Molecular analysis showed that both proteins have molecular weights consistent with their monomeric native structure. In previous studies carried out by Gandhi et al (2015) and Özcan et al (2001), the molecular mass of the recombinant α amylase from Geobacillus stearothermophilus was calculated as 59 kDa and 65 kDa from Bacillus subtilis, respectively. The molecular mass of the recombinant β amylase from barley calculated as 60 kDa by Ziegler (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of VirB10 protein in E. coli is difficult, with extremely low yields. Gandhi and colleagues demonstrated a two-fold increase in the yield of Geobacillus stearothermophilus derived SR74 recombinant β-Amylase using the P. pastoris expression system compared to an E. coli expression system [28]. …”
Section: Discussionmentioning
confidence: 99%